ANALISIS KAUSALITAS ANTARA PENDAPATAN NASIONAL DENGAN SUKU BUNGA MENGGUNAKAN METODE FINAL PREDICTION ERROR (FPE) TAHUN 1997.1 - 2003.4 - Nurani Arum W; Didit Purnomo (Muhammadiyah University Press, 2005)
The objective of this research is to verify if the national income variable influences interest rate, or vice versa, the interest rate influences national income. The research is conducted by using causality test of Final Prediction Error which is method for determining the optimal length in the way minimizing FPE.Result of the test by using FPE showed that there is one datum showing GNP stationer variable demonstrating to Mackinnon critical values 5%, the best testing model is model which having the minimum AIC, and also on interest rate of bank of Indonesia (SBI) there is one datum of stationer showing that SBI stationer on Mackinnon critical values 5% demonstrating model 3 stationer which has minimal AIC value. The conclusion acquired from this research is that GNP causes SBI but SBI does not cause GNP because GNP variable is influenced by the previous time.